Di-n-hexyl phthalate causes Leydig cell hyperplasia in rats during puberty. (10th October 2020) - Ye, Jianxin; Zhang, Kangnan; Yuan, Xindi; Ji, Haosen; Hu, Miner; Huang, Tongliang; Ge, Ren-Shan
Highlights: DNHP stimulates Leydig cell proliferation. DNHP delays Leydig cell differentiation at higher doses. DNHP down-regulates steroidogenesis-related gene expression at higher doses. Abstract: Di -n- hexyl phthalate (DNHP) is commonly used as a plasticizer. However, whether DNHP influences Leydig cell development during puberty remains unexplored. In this study, DNHP (0, 10, 100, and 1000 mg/kg) was administered via gavage to 35-day-old male Sprague-Dawley rats for 21 days. Serum levels of testosterone, luteinizing hormone, follicle-stimulating hormone, Leydig cell number, the expression of Leydig and Sertoli cell genes and proteins were investigated. DNHP significantly increased serum testosterone levels at 10 mg/kg but lowered its level at 1000 mg/kg. DNHP significantly increased luteinizing hormone levels at 1000 mg/kg without affecting follicle-stimulating hormone levels. DNHP increased Leydig cell number at all doses but down-regulated the expression of Lhcgr, Hsd3b1, Hsd17b3, and Hsd11b1 in Leydig cell per se at 1000 mg/kg. DNHP elevated phosphorylation of ERK1/2 and GSK-3β at 10 mg/kg but decreased SIRT1 and PGC-1α levels at 1000 mg/kg. In conclusion, DNHP exposure causes Leydig cell hyperplasia possibly via stimulating phosphorylation of ERK1/2 and GSK-3β signaling pathways.